2008
DOI: 10.1016/j.icarus.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Fluvial erosion and post-erosional processes on Titan

Abstract: The surface of Titan has been revealed by Cassini observations in the infrared and radar wavelength ranges as well as locally by the Huygens lander instruments. Sand seas, recently discovered lakes, distinct landscapes and dendritic erosion patterns indicate dynamic surface processes. This study focus on erosional and depositional features that can be used to constrain the amount of liquids involved in the erosional process as well as on the compositional characteristics of depositional areas. Fluvial erosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 45 publications
6
68
0
Order By: Relevance
“…Subsequent Cassini observations showed that similar channels are seen globally on all types of Titan terrain [2][3][4][5][6][7]. While some channels terminate in broad alluvial fans, like those at the spot of Huygens' touchdown, others lead to polar seas [8,9] or dry lakebeds [10,11].…”
Section: Introductionmentioning
confidence: 91%
“…Subsequent Cassini observations showed that similar channels are seen globally on all types of Titan terrain [2][3][4][5][6][7]. While some channels terminate in broad alluvial fans, like those at the spot of Huygens' touchdown, others lead to polar seas [8,9] or dry lakebeds [10,11].…”
Section: Introductionmentioning
confidence: 91%
“…The resulting theory has application to dunes on Mars, Earth, and Venus. The large fluid discharge rates inferred from some of Titan's channel systems and outflow plains [57] imply catastrophic flooding that resembles that seen on Mars and in the Channeled Scablands on Earth. Titan lakes share striking morphological similarities with Earth lakes in semi-arid regions [18,84].…”
Section: Titan's Contextmentioning
confidence: 95%
“…Ephemeral streams carve channels [155]. At the equator the streams carry sediments into low-lying plains like the Huygens landing site [57]. At the poles, runoff deposits sediment into lakes and seas [146].…”
Section: Cassini-huygens Discoveriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, in the form of the rain, it reaches the moon's sur face (Jaumann et al, 2008). Next, the liq uid, accord ing to grav ity, flows from an up per to a lower region, even tu ally form ing streams, rivers, and lakes (Lunine and Lorenz, 2009).…”
Section: Basic Information About Titanmentioning
confidence: 99%